New desires, new selves : sex, love, and piety among Turkish youth - Ozyegin, Gul, 1955- (New York University Press, 2015)
As Turkey pushes for its place in the global pecking order and embraces neoliberal capitalism, the nation has seen a period of unprecedented shifts in political, religious, and gender and sexual identities for its citizens. InÃ#x82;Â New Desires, New Selves, Gul Ozyegin shows how this social transformation in Turkey is felt most strongly among its young people, eager to surrender to the seduction of sexual modernity, but also longing to remain attached to traditional social relations, identities and histories. Ã#x82;Â Ã#x82;Â Ã#x82;Â Ã#x82;Â Ã#x82;Â Ã#x82;Â Ã#x82;Â Ã#x82;Â Ã#x82;Â Ã#x82;Â Engaging a wide array of upwardly-mobile young adults at a major Turkish university, Ozyegin links the biographies of individuals with the biography of a nation, revealing their creation of conflicted identities in a country which has existed uneasily between West and East, modern and traditional, and secular and Islamic. For these young people, sexuality, gender expression, and intimate relationships in particular serve as key sites for reproducing and challenging patriarchy and paternalism that was hallmark of earlier generations. As Ozyegin evocatively shows, the quest for sexual freedom and an escape from patriarchal constructions of selfless femininity and protective masculinity promise both personal transformations and profound sexual guilt and anxiety. A poignant and original study, Ã#x82;Â New Desires, New SelvesÃ#x82;Â presents a snapshot of cultural change on the eve of rapid globalization in the Muslim world. Ã#x82;Â Ã#x82;Â Ã#x82;Â Instructor's Guide.